Vocational Assessment of Learning Disabled Students Using the SDS-Ev - Jane L. Winer (Journal of Research in Rural Education, 1988)
Junior and senior high school students (N=25) in classes for the learning disabled in a Southwestern rural school district completed Holland's Self-Directed Search-Form E (SDS-E) with individual assistance as requested. SDS-E results are presented for the sample in terms of scale scores and personality type and as associated with students' reading level and measured intelligence. Implications for the use of the SDS-E in vocational guidance programs for learning disabled students in rural schools are discussed.